Copper(ii) complexes with tridentate Schiff base-like ligands: solid state and solution structures and anticancer activity. Issue 40 (2nd October 2019) - Dankhoff, Katja; Gold, Madeleine; Kober, Luisa; Schmitt, Florian; Pfeifer, Lena; Dürrmann, Andreas; Kostrhunova, Hana; Rothemund, Matthias; Brabec, Viktor; Schobert, Rainer; Weber, Birgit
Abstract : We report 15 new Cu(ii ) complexes with tridentate NNO β-acylenamino ligands derived from 2-picolylamine and bearing up to three alkyl, alkoxy, alkoxycarbonyl, or (pseudo)halide substituents. Abstract : We report 15 new Cu(ii ) complexes with tridentate NNO β-acylenamino ligands derived from 2-picolylamine and bearing up to three alkyl, alkoxy, alkoxycarbonyl, or (pseudo)halide substituents. The structures of nine complexes were elucidated by single crystal X-ray diffraction analysis. Complexes with an unsubstituted pyridine ring crystallised with a square pyramidal coordination sphere, whereas substitution of the pyridine ring led to a square planar coordination sphere around the metal centre. The solution structures and properties of the complexes were characterised by UV-Vis spectroscopy and cyclic voltammetry. They were also tested for their cytotoxic effect on four human cancer cell lines. Two complexes were identified that were highly active with single-digit IC50 values, exceeding those of cisplatin by far. A tentative structure–activity relationship was proposed as well as topoisomerase I inhibition as a possible mode of action, while any significant interference with DNA and the level of reactive oxygen species could be excluded.